Search for a new bottomonium state decaying to $\Upsilon(1S)\pi^+\pi^-$ in pp collisions at $\sqrt{s}$ = 8 TeV - CMS collaboration (2224 authors); Hollar, Jonathan; Nayak, Aruna; Calpas, Betty; Almeida, Nuno; Bargassa, Pedrame; Beirão Da Cruz E Silva, Cristóvão; Faccioli, Pietro; Ferreira Parracho, Pedro Guilherme; Gallinaro, Michele; Nguyen, Federico; Rodrigues Antunes, Joao; et al. (My University, 2013)
The results of a search for the bottomonium counterpart, denoted as $X_b$, of the exotic charmonium state X(3872) is presented. The analysis is based on a sample of pp collisions at $\sqrt{s}$ = 8 TeV collected by the CMS experiment at the LHC, corresponding to an integrated luminosity of 20.7 inverse femtobarns. The search looks for the exclusive decay channel $X_b \to \Upsilon(1S) \pi^+ \pi^-$ followed by $\Upsilon(1S) \to \mu^+ \mu^-$. No evidence for an $X_b$ signal is observed. Upper limits are set at the 95% confidence level on the ratio of the inclusive production cross sections times the branching fractions to $\Upsilon(1S) \pi^+ \pi^-$ of the $X_b$ and the $\Upsilon$(2S). The upper limits on the ratio are in the range 0.9-5.4% for $X_b$ masses between 10 and 11 GeV. These are the first upper limits on the production of a possible $X_b$ at a hadron collider.